Inclusive Visions for Urban Transitions: Lessons from stakeholder dialogues in Asian medium sized cities. (October 2018) - Junghans, Lisa; Kreft, Sönke; Welp, Martin
Highlights: Stakeholder dialogues can help to advance a city's work on climate change. More interaction between workshop participants leads to wider the societal consensus building. A diversity of stakeholder perspectives yields more acceptance for a transformative course of action. Political competence among workshop participants is key to put decisions into operation. Abstract: Climate change and other sustainability challenges represent a foundational contest to traditional urban development concepts and practices. Reducing greenhouse gas emissions from urban infrastructure and leading cities towards climate resilience requires a transformation of city structures, its organisation and its resident's lifestyles. To anchor such a transformative course of action, a wider societal consensus building with an active and earnest engagement with all relevant actors and interest groups in the city is required. With stakeholder dialogues being a suitable and proven instrument for stimulating engagement, this paper explores dynamics of stakeholder dialogues and how they can advance a city's work on climate change. For this purpose, a number of stakeholder dialogues with key actors in the field of climate change were organised in four cities across India, Indonesia and the Philippines. Studying them, the authors identified four dimensions that seem to shape the effectiveness and success of such dialogues: the level of interaction between the participants during the events, the diversity of perspectives represented by the stakeholders, their level of capacities in dealing with urban climate issues and, ultimately their political competence that allows them to take decisions based on workshop outcomes.